Nanofibers based on zein protein loaded with tungsten oxide for cancer therapy: fabrication, characterization and in vitro evaluation - Gomaa El Fawal; Ashraf M. Omar; Marwa M. Abu-Serie (Scientific Reports, 2023)
Abstract Plant proteins have become attractive for biomedical applications such as wound dressing and drug delivery. In this research, nanofibers from pristine zein (plant protein) and zein loaded with tungsten oxide (WO3) were prepared (WO3@zein) using less toxic solvents (ethanol and acetic acid). Morphological and biological properties of the zein nanofiber were determined. Prepared nanofibers were defined by thermogravimetric analysis (TGA), X-ray diffraction (X-RD), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy. The average fiber diameter was unchanged with an increase in WO3 concentration from 0.001 to 0.008%. FT-IR spectroscopy and X-RD indicated the presence of WO3 in WO3@zein nanofibers. In comparison to WO3-free, WO3@zein nanofibers showed higher safety and preserved the anticancer effect of WO3 against human melanoma cell line (A375) melanoma cells compared to WO3-free. Moreover, both WO3-free and WO3@zein caused a fourfold increase in the cellular proliferation of reactive oxygen species (ROS) in the treated A375 cells compared to untreated cells. ROS elevation led to apoptosis-dependent cell death of A375 cells as evidenced by up-regulating the expression of p53-downstream genes (p21 and Bax) (tumor-suppressor gene) while down-regulating the expression of key oncogenes (BCL2 and cyclin D). In conclusion, the prepared nanofiber represents a promising and safe candidate for anticancer applications.